EFFECT OF MATERNAL MIGRAINE ON CHILDREN'S QUALITY OF SLEEP - ERDOĞDU, AYŞE BURCU (LITERATURA MEDICA, 2017)
Backround and aim - Sleep disorders are common problems associated with migraine. These sleep disorders are known to have a debilitating impact on daily lives of migraine patients. The purpose of this study is to assess the effects of sleep disorders experienced by individuals suffering from migraine on their children as well as the presence of sleep disorders in their children. Materials and methods - This study included 96 mothers diagnosed with migraine and their 96 healthy children, and a control group formed of 74 healthy mothers and their children. Exclusion criteria were chronic systemic disease or central nervous system disease or a history of smoking/alcohol use for mothers, and chronic disease or regularly occurring headaches or recurrent abdominal pain for children. For maternal evaluation, the Visual Analogue Scale (VAS), Migraine Disability Assessment Scale (MIDAS), Pittsburgh Sleep Quality Index (PSQI), Beck Depression Index (BDI) and Beck Anxiety Index (BAI) were used and for the assessment of the children's quality of sleep, the Children's Sleep Habits Questionnaire (CSHQ) was used. The SPSS 21.0 program was employed for statistical analysis, with statistical significance set at p<0.05. Findings - The mean age of the group with migraine was 36.6 +/- 7.1 years, while that of the control group was 38.01 +/- 4.7. Mood and sleep disorders were more frequently observed in the participants with migraine (p<0.05). Sleep disorders were significantly low in children with migraineur mothers (p=0.02); and child sleep anxiety is significantly high in control group (p=0.048). Maternal BAI scores had a significant influence on their children's quality of sleep. Discussion and conclusion - In our study, the presence of migraine-type headache in mothers was observed to have a positive effect on reducing sleep disorders in the children. Recurrent headaches of the migraineur mothers with or without sleep disorders and psychiatric comorbidities did not influence the quality of sleep in their children directly, but the sleep anxiety of the children may have had an impact on it.
Keywords: sleep disorders; maternal migraine; CHRONIC PAIN; HEADACHE; INSTRUMENT; DISORDERS; ANXIETY; HISTORY; RISK